2015
DOI: 10.1074/jbc.m114.611178
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Two Hydrophobic Residues within Human Glucose Transporter 9 (hSLC2A9) in Substrate Selectivity and Urate Transport

Abstract: Background: A hydrophobic residue in TM7 of the hSLC2A9 was found to affect hexose transport. Results: Both Ile-335 and Trp-110 affect fructose trans-acceleration of urate, whereas only Trp-110 directly affects urate transport. Conclusion: hSLC2A9 handles urate/fructose transport differently. Significance: This study provides further information of how hSLC2A9 handling its substrates could be beneficial for future pharmaceutical treatments used in related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…3E). As published previously, we have found a quasi-linear I-V relationship from −120 to 60 mV12, indicating that the membrane voltage mainly acts as a driving force for the urate transport (Fig. 3E).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…3E). As published previously, we have found a quasi-linear I-V relationship from −120 to 60 mV12, indicating that the membrane voltage mainly acts as a driving force for the urate transport (Fig. 3E).…”
Section: Resultssupporting
confidence: 86%
“…Substitution of isoleucine into valine in the fructose transporting hSLC2As only affects fructose but not glucose transport. This hydrophobic interaction also appears to have no effect on urate transport in hSLC2A91012. These findings also support the hypothesis that hexoses and urate have different binding residues in hSLC2A9.…”
supporting
confidence: 75%
“…61 These models indicate that this hydrophobic residue (I335 in GLUT9 and I296 in GLUT5) is not projecting toward the aqueous transport pathway as previously proposed; instead, it appears to interact with residues on the adjacent TMs via an complex hydrophobic network (Figure 2). Additional functional studies confirmed that replacement of I335 in GLUT9 with valine resulted in a loss of trans-stimulation …”
Section: Importance Of Transmembrane Domain 7 In Glutsmentioning
confidence: 68%
“…60 However, analysis using a GLUT9 computer model based on the recent GLUT1 crystal structure indicates that this isoleucine is more likely to be facing away from the aqueous pore and to be acting as a structural regulator through hydrophobic interactions with adjacent TMs. 61 At the equivalent position in Class I GLUTs (except for GLUT2 which can also transport fructose) there is a valine residue. 7 This suggests that subtle interactions between TMs mediated by hydrophobic residues can affect substrate specificity within this family of transporters.…”
Section: Class II Glutsmentioning
confidence: 99%
“…In the uniporter research field, a much-studied phenomenon exists that is called trans-acceleration, 7 that is, the transport of one type of substrate (often radioisotope-labeled) from one side of the membrane can be accelerated by the existence of another type of substrate (e.g., unlabeled) on the opposite side of the membrane. In fact, this is one form of counter-flow experiment, although the two substrates on the opposite sides of the membrane may differ chemically (e.g., fructose vs. urate 11 ) or in concentration. In any of these experimental or natural processes, the inward transport is driven by the chemical potential of one substrate, whereas the outward transport is driven by the other, forming a functional cycle as a result.…”
Section: Kinetic Asymmetry Transacceleration and Othersmentioning
confidence: 99%